A study on electrical performance of N-type bifacial PV modules. (1st November 2016) - Yu, Bo; Song, Dengyuan; Sun, Zhonggang; Liu, Keming; Zhang, Ying; Rong, Dandan; Liu, Lijun
Highlights: N type bifacial PV module advantage. A bifacial module is averagely 4.03% higher than that of a regular module for micro inverter. Bifacial modules is averagely 3.21% higher than that of the regular modules for string inverter. Abstract: Transparent backsheet is adopted to encapsulate PV modules to take the advantages of the potential of N-type monocrystalline bifacial solar cells. The energy output of bifacial modules is significantly higher than that of regular modules for micro inverter and string inverter PV system at different weather conditions. The monthly energy output of a bifacial module is averagely 4.03% higher than that of a regular module for micro inverter PV system after an outdoor test lasting for six months. The monthly energy output of bifacial modules is averagely 3.21% higher than that of the regular modules for string inverter PV system after an outdoor test lasting for one year. This indicates the advantages of the application of transparent backsheet on the N-type c-Si solar cells and shows good potential in application to rooftop and household photovoltaic systems in large scale. Besides, N-type bifacial PV modules with transparent backsheet is especially suitable to those areas with good irradiance and low temperature.